2020
DOI: 10.3389/fcell.2020.570305
|View full text |Cite
|
Sign up to set email alerts
|

Circ-ZDHHC5 Accelerates Esophageal Squamous Cell Carcinoma Progression in vitro via miR-217/ZEB1 Axis

Abstract: Circular RNA (circRNA) exhibits a covalently closed circular conformation and is structurally stable. Nevertheless, the precise effects exerted by circRNA in esophageal squamous cell carcinoma (ESCC) remains uncertain. circRNA was ascertained by a human circRNA array study and was confirmed by the quantification of reverse transcriptase polymerase reactions. A luciferase reporter, fluorescence in situ hybridization experiment was exploited to explore the interaction between circ-ZDHHC5 and miR-217. The functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…Recently, whole-genome sequencing has revealed abnormal expression of several circRNAs in various tumors. Moreover, circRNAs have crucial functions in the genesis and progression of different cancers [48][49][50]. For instance, Zhao et al found that propofol blocked the tumor and aerobic glycolysis of lung cancer cells by regulating the TADA2A/miR-455-3p/FOXM1 axis [51].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, whole-genome sequencing has revealed abnormal expression of several circRNAs in various tumors. Moreover, circRNAs have crucial functions in the genesis and progression of different cancers [48][49][50]. For instance, Zhao et al found that propofol blocked the tumor and aerobic glycolysis of lung cancer cells by regulating the TADA2A/miR-455-3p/FOXM1 axis [51].…”
Section: Discussionmentioning
confidence: 99%
“…The poor outcome of ESCC is associated with its insidious initial symptoms, susceptibility to metastasis, resistance to radiotherapy, and tumor recurrence ( Pennathur et al, 2013 ). Over the past few years, multidisciplinary and surgical treatments have been developed, but the median survival of ESCC cases is only 10 months ( Wang et al, 2020a ). Moreover, considering the limited prediction of prognosis for ESCC patients, there is an urgent need for the exploration of novel biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…40 CircZDHHC5 is capable of contributing to ESCC pathogenesis depending on the circZDHHC5/miR-217/zinc finger E-box binding homeobox 1 ceRNA crosstalk. 41 Conversely, circ-Foxo3 shows reduced expression in ESCC and can impede ESCC cell malignant behavior by involving the posttranscriptional modulation of PTEN via miR-23a competition. 42 Considering the anti-ESCC activity of circ_0001946, 14 we sought to explore its ceRNA mechanism in ESCC.…”
Section: Discussionmentioning
confidence: 99%